A Sesquiterpenoid from Farfarae Flos Induces Apoptosis of MDA-MB-231 Human Breast Cancer Cells through Inhibition of JAK–STAT3 Signaling - Hyeri Jang; Hyejin Ko; Kwangho Song; Yeong Shik Kim (Biomolecules, 2019)
Triple-negative breast cancers (TNBCs) are hard-to-treat breast tumors with poor prognosis, which need to be treated by chemotherapy. Signal transducer and activator of transcription 3 (STAT3) is a transcription factor involved in proliferation, metastasis, and invasion of cancer cells. Therefore, research on searching for promising compounds with metabolism that suppress phosphorylation or transcription of STAT3 in TNBC cells is important. Farfarae Flos is well known as a traditional medicine for treating inflammation. However, few studies have shown that sesquiterpenoids from Farfarae Flos have an anticancer effect. In this study, efficient separation methods and an MTT assay were conducted to isolate an anticancer compound from Farfarae Flos against TNBC MDA-MB-231 cells. Here, 7β-(3-Ethyl-cis-crotonoyloxy)-1α-(2-methylbutyryloxy)-3,14-dehydro-Z-notonipetranone (ECN), a compound isolated from Farfarae Flos showed a potent cytotoxic effect on MDA-MB-231 cells. ECN inhibited JAK−STAT3 signaling and suppressed the expression of STAT3 target genes. In addition, ECN induced apoptosis through both extrinsic and intrinsic pathways. Furthermore, we investigated that ECN inhibited the growth of tumors by intraperitoneal administration in mice injected with MDA-MB-231 cells. Therefore, ECN can be an effective chemotherapeutic agent for breast cancer treatment.